ALGORITHMS FOR CONVERTING VOXEL 3D MODELS INTO POLYGONAL ONES - Duvanov, S. S.; Baranova, I. V. (Computer Science and Applied Mathematics, 2023)
This document explores the using of voxels today in such areas as medicine, 3D scanning, game industry and why do we need to convert them to polygonal mesh. It also describes and analyses the currently existing algorithms for converting voxel 3D models into polygonal ones. Aim of converting algorithms is extracting the surface information from the voxel grid and generate a polygonal mesh composed of triangles that approximate the original shape. The research identified about 10 existing algorithms: Marching Cubes, Dual Contouring, Surface Nets, Voxel Carving, Sparse Voxel Octree, Surface Extraction from Volume Data (SEV), Cubical Marching Squares, Adaptive Grid Subdivision, Occupancy Networks, Deep Implicit Fields. Their features, pros and cons were described. It was chosen among the converting algorithms, taking into account the simplicity, efficiency and availability of implementation, one algorithm, which can become the basis of the program for converting voxel 3d models into polygonal mesh. The choice of algorithm depends on various factors, including the desired surface quality, computational efficiency, handling of sharp features, and implementation complexity, but there were several main criteria selected. The chosen algorithm is Marching Cubes, because it is widely used, has available implementations, has good performance. Future research will focus on creating a converter program since there are currently no freely available converters that would produce a high-quality editable polygonal mesh. All existing voxel editors and online converters export the voxel 3d model into polygonal mesh without any approximation, so the export result is a cube set, poorly united into one surface with surface breaks. Export polygonal mesh models also have a problem with a large number of triangles, which makes the model hard to edit. To create a converter that solves those problems, first, we must choose an algorithm that will become the basis of the future converter. Target algorithm will be customized in future to improve the quality of output polygonal mesh comparing to the existing convertors.